Bioethical perceptions and knowledge of professors of Medicine at the Universidad San Gregorio de Portoviejo - Fernandez Velez, Yumy Estela (2025)
Bioethics constitutes an essential component in medical education, particularly in teaching practice, where values, principles, and ethical behaviors are modeled. In Ecuador, there is scarce evidence regarding the level of bioethical knowledge among university health professors. This study aimed to analyze the perceptions and bioethical knowledge of faculty members in the Medicine program at Universidad San Gregorio de Portoviejo (USGP) – Ecuador. A mixed-method, descriptive, correlational, non-experimental, and cross-sectional design was applied. A total of 26 faculty members participated, who completed a validated structured questionnaire with closed-ended questions and one open-ended question, which was qualitatively analyzed through categorical coding. Statistical analysis included measures of central tendency, frequencies, and association tests. The results showed a significant association between sex and permissiveness toward student participation without patient consent (p=0.048), with male faculty members being more permissive, thus demonstrating differentiated patterns of professional socialization. Moreover, 96% of participants expressed interest in strengthening their bioethical training. These findings highlight the need to implement institutional programs of continuous training that integrate Bioethics as a transversal axis in medical teaching, supported by evaluation and monitoring strategies that reinforce coherence between ethical discourse and educational practice.